Feasibility and Efficacy of a Degradable Magnesium-Alloy GBR Membrane for Bone Augmentation in a Distal Bone-Defect Model in Beagle Dogs. (23rd March 2022) - Yan, Zi-Yu; Zhu, Jian-Hua; Liu, Guan-Qi; Liu, Zhi-Chao; Guo, Chuan-Bin; Cui, Nian-Hui; Han, Jian-Min
Abstract : We explored the feasibility and efficacy of a degradable magnesium (Mg) alloy guided bone regeneration (GBR) in the treatment of bone defects after tooth extraction. A GBR membrane (MAR-Gide (MG)) was used to treat a mandibular second molar (M2M)-distal bone defect (DBD). In eight beagle dogs, bilateral mandibular second and fourth premolars were hemi-sected. The distal roots were removed to create a two-wall bony defect of dimension 5 mm × 5 mm × 5 mm to simulate M2M-DBD. Thirty-two bone defects were assigned randomly into four groups according to GBR membranes (MG and Bio-Gide (BG)) applied and the time of killing (3 months and 6 months after surgery). The osteogenesis of bone defects and MG degradation were analyzed using micro-CT, histology (staining, tartrate-resistant acid phosphatase), and inductively coupled plasma mass spectrometry. MG did not increase the prevalence of infection, wound dehiscence, or subcutaneous emphysema compared with those using BG. Trabecular volume/total volume at 3 months (63.71 ± 10.4% vs . 59.97 ± 8.94%) was significantly higher in the group MG than that in the group BG. Implanted MG was degraded completely within 3 months, and "island-shaped" new bone was found near MG degradation products. A significant difference was not found in vertical bone height or percent of new bone formation (45.44 ± 12.28% vs . 43.49 ± 7.12%) between the groups. The concentration of rare-earth elements in mandibular lymph nodes of the group MG was significantly higher than that of the group BG (P ≤ 0.017 ) but did not lead to histopathological changes. In summary, MG exhibited good biocompatibility and clinical applicability compared with BG in vivo. The osteogenic effect of MG could be enhanced by regulating the degradation rate of Mg-alloy.